До питання про можливості бухгалтерського обліку трансакційних витрат підприємства - Попадинець, Олена Василівна (НТУ "ХПІ", 2014)
Обґрунтовано необхідність виокремлення трансакційних витрат у системі бухгалтерського обліку підприємства та запропоновані різні підходи до класифікації їх складу за рахунками бухгалтерського обліку

The article substantiates the need for separation of transaction costs in the accounting system of the enterprise and proposed various approaches to the classification of their structure on the accounts of accounting
On the possibility of accounting transaction costs businesses
Keywords: бухгалтерський облік; витрати підприємства; трансакцйні витрати; трансформаційні витрати; витрати вимірювання; витрати виявлення альтернатив; разові трансакцій витрати; умовно-постійні трансакційні витрати; трансакційний облік; accounting; costs of enterprise; transaktsyni costs; transformation costs; measurement costs of identifying alternatives; one-time transaction costs; conventionally fixed transaction costs; transaction records